Principality of Andorra : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Principality of Andorra. (IMF Staff Country Reports; Country Report ;, 2021)
Andorra, the IMF's newest member since October 2020, participated in its first Article IV consultation with a commitment to further enhance transparency. Tourism and banking-related services dominate economic activity in the euroized economy. The country enjoys long-standing political stability, a good track-record of fiscal discipline, a gender-balanced work force, and internationally competitive ski resorts. The authorities are managing the pandemic well with universal testing and expanded hospital capacity that kept fatality rates very low despite high case-loads. The testing strategy helped Andorra implement more targeted internal restrictions than in neighboring countries. At the same time, emergency fiscal measures stabilized real incomes and supported firms.